Structural and mixing characteristics influenced by streamwise vortices in supersonic flow - Zhang, Dongdong; Tan, Jianguo; Hou, Juwei (Applied physics letters, 2017)
By utilizing nanoparticle-based planar laser scattering method, the flow structures and mixing characteristics with the existence of large-scale streamwise vortices generated by a lobed mixer are investigated experimentally. The emergence and evolution of streamwise and spanwise vortices and the interaction between these two kinds of vortical structures are clearly exhibited. Fractal analysis reveals that streamwise vortices are strongly convoluted and possess complicated three-dimensional characteristics, which can favor molecular mixing. The turbulent/non-turbulent interface is obviously present, in which drastic turbulent entrainment occurs. Moreover, the emergence of typical T-shaped vortex suggests that this kind of vortex is a usual topological structure in turbulent transition region.